TI_GERICHTE 12.2010.31 vom 29. April 2010 , Locazione - disdetta e condizioni - vendita dell'ente locato con doppio turno d'asta - TI Tribunale d'appello (2010)
Locazione - disdetta e condizioni - vendita dell'ente locato con doppio turno d'asta